Environmental Toxins and Microplastics: An In-Depth Comparative Analysis of Subtle Health Hazards" - Ameya, Lanjewar (Asian Journal of Pharmaceutical Research and Development, 2024)
This study aims to comprehensively investigate the combined toxicity of microplastics and heavy metals, with a focus on their impact on human health and the ecosystem. The research specifically explores the risks associated with ingesting microplastics containing elevated levels of heavy metals, examining their potential contribution to diseases such as cancer, reproductive disorders, neurological diseases, cardiovascular conditions, respiratory ailments, and diabetes. An exhaustive literature review synthesizes existing evidence on the individual and synergistic effects of microplastics and heavy metals. This review includes studies on the absorption of heavy metals by microplastics and their influence on human health, particularly role in diseases such as cancer, reproductive disorders, neurological diseases, cardiovascular conditions, respiratory ailments, and diabetes. Microplastics may exacerbate heavy metal absorption into the bloodstream through damage to the gut lining. Current research findings underscore the escalating concern for public health due to the combined toxicity of microplastics and heavy metals. Microplastics have been found to absorb heavy metals, potentially leading to elevated concentrations when ingested. Damage inflicted by microplastics on the gut lining may contribute to an increased risk of diseases, including cancer, reproductive disorders, neurological diseases, cardiovascular conditions, respiratory ailments, and diabetes. The observed combined toxicity poses a serious and multifaceted threat to both human health and the ecosystem. Urgent action is imperative to mitigate exposure and implement sustainable practices. The existing evidence highlights the critical need for further research to comprehend the intricate risks associated with the interaction between microplastics and heavy metals, emphasizing the urgency of addressing this emerging public health concern, including its link to diabetes.